Design of Remotely Operated Underwater Vehicle (ROUV) for Underwater Metal Detection - Widjaja, Raden Sjarief; Purwanto, Dedi Budi; Trimulyono, Andi; Hafizh, Muhammad Nur Abdullah (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2024)
The underwater surveys and inspections in Indonesia were carried out mostly by the operation of practical divers who were limited to shallow waters. The deep - sea exploration requires more advanced technology. The development of underwater technology is required to support many functions of underwater surveys and inspections. The purpose of this study was to design a Remotely Operated Underwater Vehicle (ROUV) for detecting objects with metallic materials. The ROV was designed with a Penta Tubular model and camera assistance for navigation, the JSNSR04T ultrasonic sensor to detect object distances, and the LJ12A3 inductive proximity sensor as a metal detector. ROUV rides are controlled using a keyboard with certain keywords and monitored using a smartphone. Testing the JSN-SR04T Ultrasonic sensor uses 5 variations of distance, namely 20cm, 40cm, 60cm, 80cm, and 100cm, with the detection object in the form of a plate with dimensions of 35cm x 35cm. For testing the inductive proximity sensor, the LJ12A3 type uses 3 variations of materials, namely steel plate, aluminum plates as metal objects, and PVC plates as control materials. Tests were carried out in two mediums, namely in air and underwater. Based on the results of data retrieval testing of the ultrasonic distance sensor in the air, the smallest error percentage is 0.06%, and the highest error percentage is 0.705%. In the underwater test, the error percentage was 0.49% for a distance variation of 100 cm. The ultrasonic distance sensor type JSN-SR04 cannot read distance data below 89.75 cm in water due to differences in the speed of sound propagation in different media. The Inductive Proximity Sensor can work well in air and water mediums with 100% accuracy on steel plates, aluminum plates, and PVC plates.